Determinants of company bankruptcy before and during the Covid 19 Pandemic - Haris; Sandra, Amelia (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2023)
Financial distress or financial difficulty is a condition where the company cannot fulfill its long-term and short-term obligations. If this condition is allowed to drag on, the company will either go bankrupt or be liquidated. Financial distress is measured using the Springate. The initial sample was 25 companies listed on the Indonesia Stock Exchange before 2018, of which only 22 companies were found eligible. Among them, nine companies are considered outliers. Therefore, only 13 firms were considered the effective sample. Since the study context is three years, we arrive at 39 data units finally used as the sample. The data source was obtained from the official website of the Indonesia Stock Exchange. Multiple linear regression shows that liquidity positively influences the Springate value, indicating decreased financial distress. Business diversification and leverage have no significant effect on financial distress. The conclusions may be different if different methods are used. Further research is suggested for the Zmijewski or Grover model for more convincing results. Further research can use the Zmijewski or Grover models. Plagiarism Check